Business Network Accessibility, Customer Relationship Management and Value Co-creation on Family Business Performance - Hayati Nupus; Wawan Ichwanudin (Research Horizon, 2021)
This study aims to analyze the effect of customer relationship management (CRM) capability, business network accessibility (BNA), and value co-creation (VCC) on the improvement of familial distribution network (FDN). In addition, this study also analyzes the influence of customer relationship management (CRM), familial distribution network (FDN), business network accessibility (BNA), and value co-creation (VCC) on improving marketing performance (MP). The results of the study show that the accessibility of the business network has a positive contribution to the strength of the familial distribution network and marketing performance, the strength of the family distribution network has a positive contribution to the marketing performance. In addition, the combination of social networking and customer relationship management provides a great opportunity to enrich customer interactions and provide businesses with a way to manage and measure how they use social networks while successfully attracting social customers.